2005
DOI: 10.1021/jp053605w
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Morphological and Adhesion Properties of Collagen Fibers in the Bruch's Membrane

Abstract: The Bruch's membrane is located beneath the retina in vertebrate eyes. We have used atomic force microscopy to examine the morphological and adhesion properties of collagen fibers located in different portions of the membrane. The D-periodicity of the fibers was 62.54 +/- 4.25 nm and 63.78 +/- 4.14 nm for regions away from the optic nerve and close to it, respectively. The adhesion properties of the collagen fibers were evaluated using force volume imaging on a number of different eye samples. The adhesion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Because of this, AFM is gaining popularity in ophthalmology and has been used to image other basement membranes in the eye. 1,8,9,13,24,25,46 The images obtained in the current study are similar to those acquired of other basement membranes in the eye: a dense interwoven fibrous structure separated by openings on the order of a micron.…”
Section: Discussionsupporting
confidence: 74%
“…Because of this, AFM is gaining popularity in ophthalmology and has been used to image other basement membranes in the eye. 1,8,9,13,24,25,46 The images obtained in the current study are similar to those acquired of other basement membranes in the eye: a dense interwoven fibrous structure separated by openings on the order of a micron.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, an understanding of the collagen Type II assembly represents an important first initial step on the road to the use of collagenous scaffolds in tissue engineering that might be used for cartilage replacement surgery in the future. Finally, the hierarchical self-assembly of collagen provides a methodology for constructing molecular systems into functional macroscopic materials with well-organized structures.Most knowledge about the fibrillation of fibril-forming collagens have been obtained by studying collagen Type I through a variety of techniques, such as X-ray diffraction, [5] transmission electron microscopy (TEM) [6][7][8][9] and atomic force microscopy (AFM). [10][11][12][13] From these studies it has been concluded that the fibrillation process is entropy driven, [14] and that the formation of D-banded fibrils is observed at temperatures above 21°C.…”
mentioning
confidence: 99%
“…Regional variations in adhesion properties of Bruch's membrane (located below the retina) have been related to the variable distribution of several types of collagen within the Bruch's membrane. 24 Although several types of collagen are found in the sclera, Type I is the predominant form. 12 Our adhesion data (Figure 3(a)) suggest that our AFM measurements are not influenced by local surface chemistry.…”
mentioning
confidence: 99%